Modal–Physical Hybrid System Identification of High-rise Building via Subspace and Inverse-Mode Methods - Fujita, Kohei; Fujimori, Yuhei; Takewaki, Izuru (Frontiers in Built Environment, 2017)
A system identification (SI) problem of high-rise buildings is investigated under restricted data environments. The shear and bending stiffnesses of a shear-bending model (SB model) representing the high-rise buildings are identified via the smart combination of the subspace and inverse-mode methods. Since the shear and bending stiffnesses of the SB model can be identified in the inverse-mode method by using the lowest-mode of horizontal displacements and floor rotation angles, the lowest-mode of the objective building is identified first by using the subspace method. Identification of the lowest-mode is performed by using the amplitude of transfer functions derived in the subspace method. Considering the resolution in measuring the floor rotation angles in lower stories, floor rotation angles in most stories are predicted from the floor rotation angle at the top floor. An empirical equation of floor rotation angles is proposed by investigating those for various building models. From the viewpoint of application of the present SI method to practical situations, a non-simultaneous measurement system is also proposed. In order to investigate the reliability and accuracy of the proposed SI method, a 10-story building frame subjected to micro-tremor is examined.